Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7sm01968h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical excluded volume screening in solutions of bottlebrush polymers

Abstract: Polymer bottlebrushes provide intriguing features being relevant both in nature and in synthetic systems. While their presence in the articular cartilage optimizes synovial joint lubrication, bottlebrushes offer pathways for fascinating applications, such as within supersoft elastomers or for drug delivery. However, the current theoretical understanding lacks completeness, primarily due to the complicated interplay of many length scales. Herein, we develop an analytical model that demonstrates how structural p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 92 publications
(162 reference statements)
5
49
0
Order By: Relevance
“…Recent simulations have also shown that there are significant in the concentration-dependent changes in the size of the bottlebrush polymers in solution. 87 Recent experiments by Bates et al 88 have also indicated that the conformation of the bottlebrush backbones is more 'coiled' than initially anticipated, which is consistent with our findings.…”
Section: Backbone Conformation Characterizationsupporting
confidence: 93%
“…Recent simulations have also shown that there are significant in the concentration-dependent changes in the size of the bottlebrush polymers in solution. 87 Recent experiments by Bates et al 88 have also indicated that the conformation of the bottlebrush backbones is more 'coiled' than initially anticipated, which is consistent with our findings.…”
Section: Backbone Conformation Characterizationsupporting
confidence: 93%
“…Both values are with very good agreement to the theoretical prediction given by Eq. (7). Note that the values of ρ calculated in the course of our simulations are much closer to the analytical theory results as compared to existing numerical data 35 .…”
Section: Integration Over the Wave Vector Q 1 Givessupporting
confidence: 85%
“…in expression(28), for f r = 0 , both at f c = 1 and f c = 2 we restore the universal size ratio of a linear polymer (5), whereas f c > 2 and f r = 0 gives the expression for a star polymer(7). For f c = 0 and f r = 1 we reproduce the known analytical expression of a single ring from Eq.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The validity of theoretically derived ratios ρ chain and ρ ring was confirmed in several simulation studies [15,17,18]. Polymer macromolecules of complex branched structure attract considerable attention both from academical [19,20] and applied [21,22] perspective, being encountered as building blocks of materials like synthetic and biological gels [23], thermoplastics [24], melts and elastomers [25,26]. High functionality of polymers provides novel properties with applications in diverse fields like drug delivery [27], tissue engineering [28], super-soft materials [29], and antibacterial surfaces [30] etc.…”
Section: Introductionmentioning
confidence: 65%